Buffalo Healthcare Management Practices in India - Kaur, Napinder; Iqubal, Md Asif; Toor, Jasdeep Singh (Journal of Buffalo Science, 2025)
Background and Aim: Dairy farming is one of the most important sub-sectors of the Indian farming system. Healthcare management practices play a crucial role in realising the full potential of dairying. Hence, the present study aims to analyse the adaptation of healthcare management practices by the buffalo farmers in the Punjab state of India. Materials and Methods: A sample size of 397buffalo farmers from three different agro-climatic zones —i.e., Shivalik Foothills, South-West Dry, and Central Plains—was selected using a multistage sampling technique for the year 2019. Descriptive statistics and the Chi-Square test are used for analysis. Results: Most buffalo farmers adopt general healthcare management practices such as vaccinating their buffaloes against Foot and Mouth Disease and use of anti-parasites for tick eradication, but they are not disinfecting the dairy shed at all. The farmers follow calf and udder healthcare management practices, such as providing bedding material to newborn calves, deworming calves, and udder cleaning. The chi-square test indicates a significant difference across categories regarding the adaptation or non-adoption of certain healthcare practices, such as the source of vaccination, tick solution, bedding material for calves, and deworming of calves. Conclusion: Buffalo health is not only a veterinary concern but also a socio-economic imperative. While certain healthcare management practices are universally embedded among the farmers, others are constrained by access, awareness, and resource availability, thereby introducing important equity considerations.